Corporate Debt Profile And Financial Performance Of Listed Consumer Goods Firms In Nigeria - Jabar, Adebola Abass; Akinadewo, Israel S. (Archives of Business Research, 2023)
This study examined the connectivity between corporate debt profile and financial performance of consumer goods firms in Nigeria. The corporate debt profile is captured with short term debt, long term debt and total debt while the outcome variables is capture with earnings per share and Tobin’s Q. Expo-facto design was adopted and covered 16 listed consumer goods firms in Nigeria based on the availability of data spanning from 2011 to 2020. Descriptive statistics were used to describe the variables of the study while the inferential statistics cover Pearson correlation and panel regression (random and fixed effect estimations) to analyze the proposed hypotheses of the study. Firstly, it was discovered that short- and long-term debt profile have a negative insignificant effect on financial performance captured with earnings per share of listed consumer goods firms in Nigeria to the tunes of -4.848905 (p=0.655>0.05) for short term debt and -6.150678 (p=0.785>0.05) for long term debt. Also, it was discovered that total debt profile has a positive significant effect on earnings per share of listed consumer goods firms in Nigeria with the coefficient and probability values of 4.735095 and 0.004 respectively. From the findings of this study, it was concluded that there is a statistical relationship between corporate debt profile and financial performance of listed consumer goods firms in Nigeria. Thus, it was recommended that the management of the listed consumer goods firms should maximize the functions of the risk committee formed to measure the risks involved in debt financing.